ANALISIS PRODUK KOSMETIK IMPOR TERKAIT BRAND DAN PENGARUHNYA TERHADAP PEMBELIAN KOSMETIK IMPOR DI SAMARINDA, KALIMANTAN TIMUR - Syarifah Aifa Fahira; Ahmad Zafrullah; Idfi Setyaningrum (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2020)
This study discusses about imported cosmetic products which are beauty products that are becoming a great choice for Indonesian women, where most of the imported products have higher quality brand than local products. This study uses a quantitative descriptive approach that is empirical inductive namely data collection, data analysis, based on facts and previous research in the field. This research uses a quantitative approach through a survey method and is carried out with an explanatory approach using a Likert scale. Respondents were asked to convey their level of agreement about the values and influences between the variables to be measured. The analytical method used in this study is the the method of multiple linear analysis with statistical methods using the Statistical Solution and Services (SPSS) version 24 software tools.The results of the analysis that have been done show that Brand Image has a significant effect on purchasing decisions, this result is proven by a significance value greater than 5%. Brand awareness also has a significant effect on purchasing decisions, this result is evidenced by the significance value greater than 5%. Perception of Price has a significant effect on purchasing decisions, this result is evidenced by the significance value greater than 5%.